Distribution and viability of ocular and non-ocular Chlamydia trachomatis in households in a trachoma-endemic community in Oromia, Ethiopia. - Oumer Shafi Abdurahman; Gebeyehu Bekele; Robert Butcher; Gadissa Deressa; Asanti Mumme; Munira Mohammed; Rufia Nure; Kedir Temam Nuri; Gemeda Shuka; Korso Hirpo; Katie Greenland; Esmael Habtamu; et al. (PLoS Neglected Tropical Diseases)
Background We aimed to determine the household distribution and viability of Chlamydia trachomatis (Ct) from the eyes, face, and hands during the initial two visits of a year-long fortnightly cohort study in geographically defined adjacent households. Methods/findings We enrolled 298 individuals from 68 neighbouring households in Shashemene Woreda, Oromia, Ethiopia. All individuals above 2 years of age residing in these households were examined for signs of trachoma. Swab samples were taken from the conjunctiva, faces, and hands and analysed for the presence and viability of Ct. Ct viability was determined using reverse transcription (RT) PCR. At the initial visit, out of 298 individuals, 133 (44.5%) were children aged 2-9 years. Among these children, 27/133 (20.3%) had trachomatous inflammation-follicular (TF), while 8/133 (6.0%) had trachomatous inflammation-intense (TI). Ct (omcB or pORF2) was detected in 16/133 (12.0%) eye swabs, 14/105 (13.5%) face swabs, and 11/105 (10.5%) hand swabs from children aged 2-9 years. Among these children at visit one, 12/14 (85.7%) with Ct on faces and 9/11 (81.8%) with Ct on hands also had detectable ocular Ct. The severity of the disease worsened from the first visit to the second, and no participants showed clearance of the disease within the two-week period. Ct infection was associated with TF (P = 0.002) and TI (P = 0.060). At visit one, among children aged 2-9 years, viable Ct was detected in 12/16 (75.0%) ocular, 6/14 (42.9%) face, and 4/11 (36.4%) hand swab samples. All viable Ct detected on the faces and hands were identified from individuals with viable ocular infections. Among caregivers whose child tested positive for Ct on their hands, 3 caregivers also had Ct on their hands, accounting for 20% (3 out of 15). Additionally, among caregivers whose child tested positive for Ct on their faces, 2 caregivers had Ct on their faces, which accounts for 14.3% (2 out of 14). In two participants, we detected Ct on the hands of ocular-negative children at the initial visit and later detected ocular Ct at the second visit. Conclusion/significance Using RT-qPCR assay to detect Ct omp2 mRNA to define viability offers a new, informative perspective of trachoma transmission in this community in Ethiopia. The presence of viable Ct on the faces and hands of individuals living in households with people with current ocular Ct infection supports the hypothesis that hands and faces are important routes for transmission of trachoma. This highlights the importance of targeted interventions to address these sites of Ct carriage to help interrupt transmission.